Towards a social pedagogic approach for social care. Issue 1 (30th June 2021) - Cameron, Claire; Moss, Peter; Petrie, Pat
Abstract : The term 'social care' has come to be applied in England to a variety of policies and services for children and adults deemed, for a variety of reasons, in need of support and assistance. The field to which it is applied is widely recognised to be in crisis, as demand grows, funding lags and a poorly qualified, low-paid workforce shows increasing signs of strain. The article argues that a further dimension to the crisis is the very term 'social care'. It has little substance and is of limited value in addressing the practice involved in working with children, young people and adults, while its continued use has encouraged a simplified and commodified understanding of what this work entails. The article introduces an alternative concept – social pedagogy – long established and well developed in continental Europe, which, it is argued, could provide a more substantial basis for everyday practice, and a strong foundation for future policy, including reforming the workforce. The conclusion questions whether 'social care' can play any useful role in the evolution of policy and practice, discussing some issues that a turn to a social pedagogic approach might raise.